2007
DOI: 10.1080/10963758.2007.10696896
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Restaurant Websites and Hospitality School Restaurant Websites

Abstract: This is a comparative analysis of industry restaurant websites and academic restaurant websites. The sites were evaluated with over 400 individual criteria in seven major categories including: technical specifications, technology used, site attractiveness, ease of navigation, ease of contact, marketing effectiveness, and legal compliance. This study highlights the areas where the sites are performing well, and those areas in need of improvement. By creating an index it is possible to compare industry and acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The role of web site personality, utilitarian and hedonic web browsing 1. Introduction Previous studies (Law et al, 2014;Berezina et al, 2012;Powley et al, 2004;Cobanoglu et al, 2011;Moreo et al, 2007;Cobanoglu et al, 2013) indicate that information technology advancement has substitutional impact on tourism and hospitality industry sector and subsequently boosts online sales of travel agencies and other reservation services (Kim et al, 2012Moreno et al, 2015;Zhao et al, 2014;Park et al, 2003).…”
Section: Online Impulse Buying Of Tourism Productsmentioning
confidence: 99%
“…The role of web site personality, utilitarian and hedonic web browsing 1. Introduction Previous studies (Law et al, 2014;Berezina et al, 2012;Powley et al, 2004;Cobanoglu et al, 2011;Moreo et al, 2007;Cobanoglu et al, 2013) indicate that information technology advancement has substitutional impact on tourism and hospitality industry sector and subsequently boosts online sales of travel agencies and other reservation services (Kim et al, 2012Moreno et al, 2015;Zhao et al, 2014;Park et al, 2003).…”
Section: Online Impulse Buying Of Tourism Productsmentioning
confidence: 99%
“…Kim, Kim, and Han (2007) examined the perceptions of potential customers of seven online travel agencies through an online survey, and identified low fares and security as being the most important website attributes. To create a ''best practice'' standard for restaurant website analysis, Moreo, Cobanoglu, and DeMicco (2007) compared industry and academic restaurant websites by evaluating over 400 individual criteria in seven major categories.…”
Section: Journal Of Travel and Tourism Marketingmentioning
confidence: 99%
“…Previous research has shown that websites can be an important tool for hospitality and tourism marketing (Aaberge et al, 2004;Bai et al, 2006;Beldona and Cai, 2006;Law and Bai, 2008;Litvin et al, 2004;Park and Gretzel, 2007). However, great variations exist in restaurant companies' capabilities in using available and effective technology applications to optimize the marketing potential through the internet (Moreo et al, 2007). Oftentimes, restaurant companies are found in a position of embracing the presence of a company website as the complete internet marketing solution.…”
Section: Introductionmentioning
confidence: 99%